Management of Sustainable Development and Its Impact on the Performance of Government Institutions in Iraq - Nursaid Nursaid; Fareed Hussein Ahmed; Tatyana Antolyevna Makrina (UIN Sunan Gunung Djati, 2023)
The research aims to influence the management of sustainable development represented in (the environmental dimension, the economic dimension, the social dimension, and the technological dimension) in government institutions represented (planning, organization, direction, and control) in the College of Administration and Economics, where the research sample was chosen to include a number of The staff of the college, has developed (90) questionnaires for both genders, returned (86) subject to statistical work, where the results showed a positive impact of sustainable development management in government institutions. Significant relationship between the technological dimension and the institution's performance. The results of the research show that there is a relationship between the economic dimension, the social dimension, Â the environmental dimension, and the performance of the institution and the institution's performance.